ENGLISH FOR TOURISM UNTUK PEDAGANG DI KAWASAN PANTAI BANDULU UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI JUAL BELI - Nasution, Sukma Septian; Kusumoriny, Laksmy Ady; Sitepu, Setiana Sri Wahyuni (Journal of Community Research and Service, 2022)
Community service underpinned within English for tourism is rarely conducted to the practitioners. Whereas, it is urgent to do that residents living in the tourism spots and are intensely mingled in the tourism services need knowledge and skills in both communication and tourism insights. These skills will be helpful for them to interact more potential tourists to come. One of them is the tourist attraction of Bandulu beach, Anyer, Banten. In connection with this, concrete steps to provide practical English training for residents around the tourist area must be implemented immediately to improve English proficiency which is one of the reasons why the tourists visit the tourist attraction. Local government data states that only 1-5% of visitors to Bandulu beach tourism are foreign tourists. That is, if in 1 month there are 1000 visitors then only 10 to 50 foreign tourists. In fact, Wiyatno (2013) stated that foreign tourist visits to Indonesia have increased almost every year. The potential number of foreign tourists should be supported by human resources with tourism insight and proficiency in foreign languages, especially good English so that communication with general English in the tourism sector can be carried out. Master, P. (1998,) said the need for mastery of English is increasing along with the need for professionals in the tourism sector. From the results of a brief interview with one of the food vendors on Bandulu Beach, communication failures often occur when foreign tourists ask for information on traditional Betawi food available around this tourist spot. The limitations of the surrounding community to communicate in English made foreign tourists not get a satisfactory answer. This problem will have a negative impact in the form of a lack of interest in the tourist attraction, especially for foreign tourists. therefore, English for Tourism for traders in Bandulu Beach is urgent to be implemented.